Socialism in its place. The «social organization» of the nation and the intersocial origins of the first Mexican socialism towards 1850 - González, Matías X. (Universidad Pedagógica y Tecnológica de Colombia, 2021)
The objective of this article is to problematize the hypotheses that have structured the study of the world of labor in Mexico in the mid-19th century and its relationship with the political language of the nation, in particular, the liberal. The complicated hypothesis of the «impossible reception» of socialism in the Mexican world of labor in the 19th-century will be the starting point for the development of an interconnection between the historiography of the world of Mexican labor and the conceptual history of the last decades. Through a discussion with the proposal of the «slip of citizenship», this article seeks to deepen the historical ridge carved out by the concepts of nation which interpose the hegemonic vision supported by the language of state nationality of the mid-19th century. In fact, with the creation of the Mexican «language of labor» other slips of the language of the nation took place, which debunk it from the homogenous view underpinned by the liberal language of the nation. As it is the product of an interaction that constituted an «intersocial milieux», through which the Mexican language of labor and French socialism communicated, it is also a fundamental condition for our understanding of the modern hybrid dimension of the Mexican nation leading up to 1850.